Innovative approach for experimental investigation and monitoring and warning of the evolutionary patterns of dam body failure in earth dams - Yunqian Xu; Tengfei Bao; Shu Zhang; Mingdao Yuan (Scientific Reports)
Abstract Dam safety is critical for protecting downstream lives, property, ecosystems, and socio-economic stability. Investigating dam breach mechanisms and establishing safety warning thresholds hold significant scientific and practical value. This study conducted dam breach model tests under diverse conditions and developed a monitoring and warning system using high-precision inclinometers to elucidate deformation characteristics and failure mechanisms. Experimental results revealed three distinct failure stages: tension cracking, localized soil flow/collapse, and catastrophic collapse/landsliding. Precursor phenomena such as seepage and cracking were observed prior to soil flow failure, suggesting that rapid infiltration line reduction during this phase could mitigate large-scale failures. Tilting deformation of the downstream slope was identified as a viable early warning indicator. An improved tangent angle method subdivided the rapid deformation stage into three substages (early, middle, and late) using thresholds of 45°, 80°, and 85°, respectively, to establish tiered warning criteria. Additionally, a reciprocal velocity method was proposed to predict breach timing by characterizing the relationship between the inverse rate of slope angle change and time, demonstrating effective breach time prediction.